COVID-19: dealing with ventilator shortage. Issue 6 (13th December 2022) - Santini, Alessandro; Messina, Antonio; Costantini, Elena; Protti, Alessandro; Cecconi, Maurizio
Abstract : Purpose of review: To describe different strategies adopted during coronavirus disease 2019 pandemic to cope with the shortage of mechanical ventilators. Recent findings: Short-term interventions aimed to increase ventilator supply and decrease demand. They included: redistributing and centralizing patients, repurposing operating rooms into intensive care units (ICUs) and boosting ventilator production and using stocks and back-ups; support by the critical care outreach team to optimize treatment of patients in the ward and permit early discharge from the ICU, ethical allocation of mechanical ventilators to patients who could benefit more from intensive treatment and short term ICU trials for selected patients with uncertain prognosis, respectively. Long-term strategies included education and training of non-ICU physicians and nurses to the care of critically-ill patients and measures to decrease viral spread among the population and the progression from mild to severe disease. Summary: The experience and evidence gained during the current pandemic is of paramount importance for physicians and law-makers to plan in advance an appropriate response to any future similar crisis. Intensive care unit, hospital, national and international policies can all be improved to build systems capable of treating an unexpectedly large number of patients, while keeping a high standard of safety.